Pendampingan Penyusunan SOP Administrasi Perpajakan Dana Desa Sesuai UU Harmonisasi Peraturan Perpajakan Untuk Meningkatkan Akuntabilitas Desa - Nuswantara, Dian Anita; Dr. Dewi; Venusita, Lintang (Universitas Negeri Surabaya, 2023)
Compliance with laws and regulations is one indicator of village accountability. This rule is not only related to village financial management regulations but also includes taxation rules. Increasing economic transactions using village funds in each village area requires an increased understanding of taxes, so it is deemed necessary for village officials in general, as well as village treasurers in particular, to obtain adequate knowledge related to taxation aspects in transactions related to the use of village funds. This Community Service (PKM) activity is aimed at increasing the understanding of village officials on the administrative procedures of Village Fund Taxation through training and assistance in the preparation of village fund tax administration SOPs. The results of the PKM activity show that on average the activity participants consisting of village officials have understood the role and importance of village fund tax administration SOPs as supporting village fund management activities. And through mentoring activities, the participants have been able to prepare village fund tax administration SOPs. With the availability of SOPs, it is expected to increase the accountability of village fund management, especially related to tax obligations.